Study on the Dynamic Safety Sactor Control of Clamping Force of Automotive Continuously Variable Transmission - Zhang Bojun; Wang Qian; Hao Yunzhi (Jixie chuandong)
Traditional constant safety factor method and novel slip-control method are extreme different methods of clamping force control strategy for continuously variable transmission（CVT）.To integrate advantages of both methods,clamping force control strategy base on dynamic safety factor is presented.Analysis of the theoretical clamping force relevant parameters and engine torque wave characteristics is carried out.The safety factor is determined according to engine torque variation trend and range.The calculating process of dynamic safety factor method is described.The simulation and experiment results show that,by adopting dynamic safety factor method,the transmission reliability is ensured.The performances of clamping-force and fuel efficiency are improved.Especially,the clamping force reduced about 20%,the economical efficiency increased about 3%.